STRUCTURAL AND FUNCTIONAL DISORDERS OF THE THYROID GLAND IN DIFFERENT TYPES OF LARYNGEAL CANCER TREATMENT - I. N. Vorozhtsova; M. R. Mukhamedov; M. A. Cherkasova; V. N. Latypova (Бюллетень сибирской медицины, 2014)
The thyroid gland is an important endocrine organ, which has a significant influence on human organism from the perinatal period and throughout the whole life, participating in the regulation of metabolism. The most common variant of thyroid dysfunction is hypothyroidism, which causes different disorders in various organs and systems, including psycho-emotional sphere. This can burden comorbidities and particularly malignant processes.Laryngeal cancer is the most common type of head and neck cancer. Despite the visual availability of this localization for diagnosis, more than 50% of cases stay timely unrecognized. Many cases are found out at stages III and IV, which requires expanded operations and causes traumatization because of disruption or loss of such important functions as breathing, swallowing, speech, causing long-term or permanent disability. This makes laryngeal cancer significant medical and social and economic problem.One of the leading treatments for cancer of the larynx is external beam radiotherapy. Thyroid gland gets into the radiation area and may take more than 50% of the total focal dose. The most common outcome of post-radiation inflammation is fibrosis of thyroid tissue due to lesions of the blood vessels and destruction of thyrocytes. It causes the development of hypothyroidism, which exacerbate stress caused by cancer and by aggressive antitumor therapy. Also, hypothyroidism adversely affects the patients’ condition during the postoperative period.Despite the fact that the diagnosis of hypothyroidism is pretty simple, and replacement therapy with L-thyroxine is cheap and available, many doctors don’t monitorthyroid function in cancer patients at all or don’t make all necessary tests.Thus, timely detection of hypothyroidism is extremely important during and after the treatment of laryngeal cancer. Early prescribing adequate treatment helps to reduce the incidence of complications.